On the Darboux integrability of a cubic CRN model in R5. (January 2016) - Ferragut, Antoni; Valls, Claudia
Abstract: We study the Darboux integrability of a differential system in R 5 with parameters coming from a chemical reaction model. In particular, we find all its Darboux polynomials and exponential factors and we prove that it is not Darboux integrable.